Management of bilateral cervical headache with right-sided cooled radiofrequency ablation of the second and third cervical median branch - Maitri Manish Shah; Aanchal Sharma; Akhil Bhalla; Sasmit Dipak Lotliker; Sidharth Verma (Indian Journal of Pain, 2023)
This report describes a case of bilateral cervicogenic headache treated with cooled radiofrequency ablation (RFA). The case is considered to review a longstanding cervicogenic headache and the use of cooled RFA of cervical facet joint as a treatment of choice. In this case, a 50-year-old female patient with intermittent dull aching bilateral headache in occipital, temporal, and cervical region for 20 years was diagnosed with bilateral greater occipital neuralgia. She underwent cooled RFA of unilateral right-sided 3rd occipital nerve (cervical 2/3 facet joint) with minimal or no side effects and 100% pain reduction at 24 h of follow-up. After 4 weeks of follow-up, the patient reported a single incident where she experienced pain that settled with medication and had a lower intensity as compared to that which was experienced before the procedure. Cooled RFA of the cervical facet joint in challenging cases can be a line of treatment to alleviate pain with lower side effects and potential for long-term efficacy.